Education, decolonisation and international development at the Institute of Education (London): a historical analysis. (22nd June 2022) - Unterhalter, Elaine; Kadiwal, Laila
Abstract : In this article, we review the process of building relationships around education and international development at IOE (Institute of Education), UCL's Faculty of Education and Society (University College London, UK). The analysis looks at how hierarchies linked to colonialism were inscribed in initial structures, and unevenly and disparately contested by students, staff and a range of interlocutors around the world over one hundred years. The article considers how this history shapes practice in the present and perspectives on the future. In describing and reflecting on processes for change, the article considers some of the questioning, discussion and new forms of relationship that are emerging as part of trying to develop an orientation away from a colonial past. Efforts to decolonise education have raised questions and actions associated with reimagining practice. We reflect on what we have learned and unlearned from our efforts to promote decolonial, socially just alternatives.